Transient serum exposure regimes to support dual differentiation of human mesenchymal stem cells - France, L.A.; Scotchford, C.A.; Grant, D.M.; Rashidi, H.; Popov, A.A.; Sottile, V. (Wiley, 2014)
Human mesenchymal stem cells (MSCs), which can generate both osteoblasts and chondrocytes, represent an ideal resource for orthopaedic repair using tissue-engineering approaches. One major difficulty for the development of osteochondral constructs using undifferentiated MSCs is that serum is typically used in culture protocols to promote differentiation of the osteogenic component, whereas existing chondrogenic differentiation protocols rely on the use of serum-free conditions. In order to define conditions which could be compatible with both chondrogenic and osteogenic differentiation in a single bioreactor, we have analysed the efficiency of new biphasic differentiation regimes based on transient serum exposure followed by serum-free treatment. MSC differentiation was assessed either in serum-free medium or with a range of transient exposure to serum, and compared to continuous serum-containing treatment. Although osteogenic differentation was not supported in the complete absence of serum, marker expression and extensive mineralization analyses established that 5 days of transient exposure triggered a level of differentiation comparable to that observed when serum was present throughout. This initial phase of serum exposure was further shown to support the successful chondrogenic differentiation of MSCs, comparable to controls maintained in serum-free conditions throughout. This study indicates that a culture based on temporal serum exposure followed by serum-free treatment is compatible with both osteogenic and chondrogenic differentiation of MSCs. These results will allow the development of novel strategies for osteochondral tissue engineering approaches using MSCs for regenerative medicine.